A Relação entre o design e a ilustração: produção de um mini guia para novos ilustradores - Ferreira, Gabriel da Silva (2022)
The relationship between design and illustration has long been undeniable, as the two areas have a great connection when it comes to visually communicating some information and showing the solution to various problems. This can be seen from some points within the history of different civilizations and cultures and later different societies. Furthermore, the work of the illustrator and the designer are related, like so many other creative professions, through doing, processes and methodologies. Taking into account all these relationships, the work aims to unravel a little more the design-illustration relationship, through historical and methodological analyses, to have a base material for the production of a mini informative guide/independent publication that helps new illustrators to find themselves within the illustration market. The mini guide brings information about concepts and methodologies about illustration, experiences, and experiences of the author and other professional designer-illustrators to understand a little more about this link between the two areas, as well as tips about the job market in the field of illustration, a little about illustration and the local market, illustration research materials and illustration practice materials.